Risk Factors for Bacterial Contamination of Bovine Meat during Slaughter in Ten Indonesian Abattoirs - Diyantoro; Dhandy Koesoemo Wardhana (Veterinary Medicine International)
Provision of beef meat which does not exceed the maximum microbial contamination limit is expected to meet the requirements to obtain safe, healthy, wholesome, and halal beef. Bacterial contamination during slaughtering process is a safety problem and concern for shelf life in meat production. This study was designed to determine the value of microbial contamination and its risk factors at the stage of the slaughtering process in the abattoirs. This research was conducted by visual observation accompanied by questionnaires and laboratory examination for bacterial contamination testing. The results showed the factor that significantly affected the total plate count (TPC) was carcass cutting (mean: 0.46 × 106 CFU/g; p=0.035) which was not carried out by the abattoir. The factor that had the greatest effect on the MPN of Escherichia coli was blood removal on the floor position (mean: 40.34 × 106 CFU/g; p=0.039) while the factors that significantly affected Staphylococcus aureus contamination were blood removal on the floor position (mean: 52.88 × 106 CFU/g; p=0.025) and carcass cutting which were not carried out by the abattoir (mean: 66.42 × 106 CFU/g; p=0.015).